POSSIBILITY OF CANDIDACY AND PARTY AFFILIATION OF INELIGIBLE INDIVIDUALS AND WITH POLITICAL RIGHTS SUSPENDED IN LIGHT OF SUMMARIES 19, 69 AND 70 OF THE TSE AND RELEVANT LEGISLATION - Mariano, Jonas; Rezende, Vinicius; Freitas, Lúcio; Fernandes Neto, Raimundo (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2024)
This article explores the interaction between ineligibility and suspension of political rights in the context of Brazilian Electoral Law. Focusing on the fictitious cases of Josias and Jéssica, convicted for abuse of power and administrative improbity, respectively. The study analyzes the applicability of electoral norms to determine their eligibility in the 2024 elections. The investigation considers Complementary Law No. 64/1990, Law No. 14.230/2021, the Political Parties Law, and Summaries No. 19, 69, and 70 of the Superior Electoral Court. The methodology includes document analysis and review of relevant case law to evaluate the compatibility between ineligibility periods and the possibility of party affiliation. The central hypothesis is that, even after convictions, the new electoral norms allow for the reintegration of individuals into the electoral process, conditioned on the fulfillment of legal deadlines. The analysis reveals the necessity of specific intent to configure administrative improbity and examines party affiliation during periods of ineligibility and suspension of political rights.